Live a Carefree Life with Trouble-Free Plastics! - Dow Chemical Company (1953)
Color print advertisement for Boltaflex vinyl plastic, made with Saran plastic produced by Dow Plastics. The advertisement features a photographic collage of summer-themed applications of Boltaflex, including the interior of a convertible, a plastic kiddie pool, an inflatable beach ball and patio furniture. The accompanying text describes a variety of applications for Boltaflex vinyl plastic and other Saran plastic products. This advertisement appeared in the June 27, 1953 edition of The Saturday Evening Post.
Keywords: Advertising; Dow Chemical Company; Plastics; Plastics industry and trade; Textile fabrics; Textile industry; Women in advertising; Children in advertising; House furnishings